Effects of birth weight, gestational age, and maternal obstetric history on birth prevalence of cerebral palsy. Issue 10 (October 1987) - Pharoah, P O; Cooke, T; Rosenbloom, L; Cooke, R W
Abstract : A register of children with cerebral palsy born to mothers resident in the Mersey region from 1966 to 1977 was compiled from health service records. Frequency distributions and prevalences of birth weight and gestational age differed for those with hemiplegia, diplegia, and quadriplegia. In particular, the children with diplegia showed a bimodal frequency distribution. Children of normal birth weight with diplegia had a higher prevalence of severe mental retardation than those of low birth weight. These differences may be due to survival bias and may not be of aetiological importance. Furthermore, the mothers of diplegic infants had a significantly higher proportion of spontaneous abortions, stillbirths, and low birthweight infants in their obstetric history. This suggests that prenatal factors predominate in the aetiology of diplegia.